Abnormal regional homogeneity and amplitude of low frequency fluctuation in chronic kidney patients with and without dialysis - Yu, Huan; Zhang, Chaoyang; Cai, Yan; Wu, Ning; Duan, Kai; Bo, Wenwei; Liu, Ying; Xu, Zitong (Frontiers in Neuroscience, 2022)
Purpose: The study characterizes homogeneity (ReHo) and amplitude of low frequency fluctuations (ALFF) in abnormal regions of brain in patients of chronic kidney disease (CKD). Materials and Methods: 64 patients of CKD were divided into 26 cases of non-dialysis-dependent chronic kidney disease (NDD-CKD), and 38 cases of dialysis-dependent chronic kidney disease (DD-CKD). 43 healthy controls (normal control, NC) were also included. All subjects underwent resting-state functional magnetic resonance imaging (rs-fMRI). ALFF and ReHo data was processed for monitoring the differences in spontaneous brain activity between the three groups. ALFF and ReHo values of extracted differential brain regions were correlated to the clinical data and cognitive scores of CKD patients. Results: NDD group has increased ALFF levels in 13 brain regions while that of DD group in 28 brain regions as compared with NC group. ReHo values are altered in 6 brain regions of DD group. ALFF is correlated with urea nitrogen and ReHo with urea nitrogen and creatinine. DD group has altered ReHo in 2 brain regions compared with NDD group. The differences are located in basal ganglia, cerebellar and hippocampus regions. Conclusion: Abnormal activity in basal ganglia, cerebellar and hippocampal regions may be involved in the cognitive decline of CKD patients. This link can provide theoretical basis for understanding the cognitive decline.